2019
DOI: 10.1074/jbc.ra119.009494
|View full text |Cite|
|
Sign up to set email alerts
|

Engineered protein disaggregases mitigate toxicity of aberrant prion-like fusion proteins underlying sarcoma

Abstract: Edited by Paul E. Fraser FUS and EWSR1 are RNA-binding proteins with prion-like domains (PrLDs) that aggregate in amyotrophic lateral sclerosis (ALS) and frontotemporal dementia (FTD). The FUS and EWSR1 genes are also prone to chromosomal translocation events, which result in aberrant fusions between portions of the PrLDs of FUS and EWSR1 and the transcription factors CHOP and FLI. The resulting fusion proteins, FUS-CHOP and EWS-FLI, drive aberrant transcriptional programs that underpin liposarcoma and Ewing's… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
39
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
3
1

Relationship

3
7

Authors

Journals

citations
Cited by 39 publications
(40 citation statements)
references
References 82 publications
(151 reference statements)
1
39
0
Order By: Relevance
“…High‐content screening has identified small molecules that modulate SG assembly, prevent accumulation of aggregation‐prone proteins in SGs and block protein aggregation and rescue neurodegenerative phenotypes . Moreover, a HSP104‐based disaggregase has been shown to attenuate phase separation of EWS‐FLI and FUS‐CHOP and reduce their toxicity in yeast models . Better understanding of biomolecular condensate regulation, with considerations for their phase behaviors and biophysical properties along with the development of innovative tools to manipulate or control them, will offer crucial insights into their functional roles, disease phenotypes and new treatment options.…”
Section: Resultsmentioning
confidence: 99%
“…High‐content screening has identified small molecules that modulate SG assembly, prevent accumulation of aggregation‐prone proteins in SGs and block protein aggregation and rescue neurodegenerative phenotypes . Moreover, a HSP104‐based disaggregase has been shown to attenuate phase separation of EWS‐FLI and FUS‐CHOP and reduce their toxicity in yeast models . Better understanding of biomolecular condensate regulation, with considerations for their phase behaviors and biophysical properties along with the development of innovative tools to manipulate or control them, will offer crucial insights into their functional roles, disease phenotypes and new treatment options.…”
Section: Resultsmentioning
confidence: 99%
“…An intriguing and emerging property of proteins containing PrLDs, such as FET proteins, is the ability to form phase-separated biomolecular condensates (Banani et al, 2017;Maharana et al, 2018;Ryan et al, 2019;Shin et al, 2017). As such, FET proteins can phase separate under physiological conditions, and perhaps most interestingly, these intrinsically disordered regions (IDRs) can be post-translationally modified to promote or prevent phase separation and other intermolecular interactions.…”
Section: Discussionmentioning
confidence: 99%
“…Despite progress in the treatment of ES, the survival rate of ES remains poor 13 . Most patients diagnosed with ES have a chromosomal translocation 14 . Some researchers have reported that chromosomal translocation can facilitate widespread epigenetic alterations 15 .…”
Section: Discussionmentioning
confidence: 99%